Comparative Study About Different Doses of Remimazolam in Short Laparoscopic Surgery: A Randomized Controlled Double-Blind Trial - Luo L; Jiang J; Zhang M; Guo Z; Zhang X; Wang F; Yang F (Dove Medical Press, 2023)
Li Luo,1 Jiduan Jiang,2 Min Zhang,1 Zhiqiang Guo,1 Xianzheng Zhang,1 Fenglin Wang,1 Fan Yang1 1Department of Anesthesiology, Suining Central Hospital, Suining City, Sichuan Province, People's Republic of China; 2Department of Anesthesiology, Suining First People's Hospital, Suining City, Sichuan Province, People's Republic of ChinaCorrespondence: Fan Yang, Department of Anesthesiology, Suining Central Hospital, Suining City, Sichuan Province, 629000, People's Republic of China, Email yanglifan2@163.comObjective: To study the efficacy and safety of different doses of remimazolam used for induction and maintenance in short laparoscopic surgery.Methods: A randomized controlled trial was conducted between May 2021 and May 2022 on patients underwent laparoscopic surgery for 30 minutes to an hour. Based on the drug used and the infusion rate, included patients were allocated into the Low-group of remimazolam (using a constant infusion rate of 6.0 mg/kg/h for induction and the rate of 1 mg/kg/h for maintenance), the Median-group (9.0 mg/kg/h for induction, 2 mg/kg/h for maintenance), the High-group (12.0 mg/kg/h for induction, 3.0 mg/kg/h for maintenance), and the Propofol group. The postoperative extubation time was used as the primary outcome.Results: A total of 192 patients were included in the study, with 47, 48, 48, and 49 patients in the Low-, Median-, High-, and Propofol group, respectively. There was a significant difference in postoperative extubation time, with the High-group having the highest duration of 15.21± 2.34 minutes compared to the Median-group (13.17± 1.71 minutes, p< 0.001), Low- group (12.72± 1.31 minutes, p< 0.001), and the Propofol group (12.24± 1.23 minutes, p< 0.001). No significant difference was found between the Low-group and the Propofol group, while the Median-group still showed higher postoperative extubation time compared to the Propofol group (p=0.008).Conclusion: Compared to propofol, total intravenous induction and maintenance with high and median dosages of remimazolam may prolong postoperative extubation time. Remimazolam can be safely used for induction and maintenance at various doses while not increasing the likelihood of adverse events.Keywords: remimazolam, propofol, general anesthesia, extubation time, laparoscopic surgery